Les enjeux locaux de la « reconstitution des peuples indiens » au Mexique - Nicolas Ellison (Cahiers des Amériques Latines)
This article – based on a field study (2000-2003) of the ethnic-ecological Totonac Indian movement of east-central Mexico – aims to demonstrate how the Chiapas conflict reference and the appropriation of indigenous rights and sustainable development discourses are made use of by Indian organizations, the Church and political parties in order to reassess minorities and their relationship to the authorities. Political competition and socio-economic discrepancies, far from being somehow “gated communities”, thus paradoxically help to redefine territorial belonging and protect the Totonacs’ restricted autonomy against outer powers.